2016
DOI: 10.1007/s00436-016-5304-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and multilocus sequence analysis of potentially zoonotic Giardia spp. from humans and dogs in Jamaica

Abstract: Giardia spp. are the causative agents of intestinal infections in a wide variety of mammals including humans and companion animals. Dogs may be reservoirs of zoonotic Giardia spp.; however, the potential for transmission between dogs and humans in Jamaica has not been studied. Conventional PCR was used to screen 285 human and 225 dog stool samples for Giardia targeting the SSU rDNA gene followed by multilocus sequencing of the triosephosphate isomerase (tpi), glutamate dehydrogenase (gdh), and β-giardin (bg) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 51 publications
4
5
0
Order By: Relevance
“…However, the distribution of assemblages A and B in humans varies among studies, the assemblage B seems to be slightly more common in both developing and developed countries than assemblage A (Yang et al 2010; Feng and Xiao, 2011; Mukherjee et al 2013; Durigan et al 2014; Minetti et al 2015 a ; Prystajecky et al 2015; Ramírez et al 2015; Forsell et al 2016). On the other hand, there are some recent studies that have instead shown a predominance of assemblage A (Coronato Nunes et al 2016; Hatam-Nahavandi et al 2016; Lee et al 2017), which are in agreement with our results.…”
Section: Discussionsupporting
confidence: 94%
“…However, the distribution of assemblages A and B in humans varies among studies, the assemblage B seems to be slightly more common in both developing and developed countries than assemblage A (Yang et al 2010; Feng and Xiao, 2011; Mukherjee et al 2013; Durigan et al 2014; Minetti et al 2015 a ; Prystajecky et al 2015; Ramírez et al 2015; Forsell et al 2016). On the other hand, there are some recent studies that have instead shown a predominance of assemblage A (Coronato Nunes et al 2016; Hatam-Nahavandi et al 2016; Lee et al 2017), which are in agreement with our results.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, due to the high prevalence of Giardia among children, and its higher exposure to dogs in poor seting, it is believed that Giardia has developed zoonotic transmission. This possibility has been reported concordantly by genotyping and molecular studies from Mexico [40], Jamaica [41], and Cambodia [42].…”
Section: Incidence and Burden Of Diseasesupporting
confidence: 61%
“…For example, the high prevalence of D and C/D in the hunting dogs in our study can be explained by living conditions and behavior favorable for feco-oral transmission, introduction of dogspecific assemblages due to more contact with canids than with humans, and the relatively low prevalence of Giardia in the Dutch human population [44,45]. Also, this may explain, at least partly, the reports of high versus low risks of zoonotic transmission [7,39,46,47].…”
Section: Discussionmentioning
confidence: 65%